Decreased Delivery of Inappropriate Shocks Achieved by Remote Monitoring of ICD: A Substudy of the ECOST Trial. (10th April 2014) - GUÉDON‐MOREAU, LAURENCE; KOUAKAM, CLAUDE; KLUG, DIDIER; MARQUIÉ, CHRISTELLE; BRIGADEAU, FRANÇOIS; BOULÉ, STÉPHANE; BLANGY, HUGUES; LACROIX, DOMINIQUE; CLÉMENTY, JACQUES; SADOUL, NICOLAS; KACET, SALEM; on behalf of the ECOST trial Investigators
Inappropriate Shocks Reduction by Remote ICD Monitoring Introduction Inappropriate shocks remain a highly challenging complication of implantable cardioverter defibrillators (ICD). We examined whether automatic wireless remote monitoring (RM) of ICD, by providing early notifications of triggering events, lowers the incidence of inappropriate shocks. Methods and results We studied 433 patients randomly assigned to RM (n = 221; active group) versus ambulatory follow‐up (n = 212; control group). Patients in the active group were seen in the ambulatory department once a year, unless RM reported an event requiring an earlier ambulatory visit. Patients in the control group were seen in the ambulatory department every 6 months. The occurrence of first and further inappropriate shocks, and their causes in each group were compared. The characteristics of the study groups, including pharmaceutical regimens, were similar. Over a follow‐up of 27 months, 5.0% of patients in the active group received ≥1 inappropriate shocks versus 10.4% in the control group (P = 0.03). A total of 28 inappropriate shocks were delivered in the active versus 283 in the control group. Shocks were triggered by supraventricular tachyarrhythmias (SVTA) in 48.5%, noise oversensing in 21.2%, T wave oversensing in 15.2%, and lead dysfunction in 15.2% of patients. The numbers of inappropriate shocks delivered per patient, triggered by SVTA and by lead dysfunction, were 74% and 98% lower, respectively, in the active than in the control group. Conclusion RM was highly effective in the long‐term prevention of inappropriate ICD shocks.